Epidemiological characteristics, clinical profile and nutritional status of hospitalized under five children - Ahmad, Kamran; Faridi, M. M. A.; Srivastava, Geetika (International Journal Of Community Medicine And Public Health, 2020)
Background: Malnutrition accounts for 68.2% of the total under-5 deaths in India, and is an important underlying risk factor for morbidity in all ages, responsible for 17.3% of the total disability-adjusted life years. Objective was to find out prevalence of moderate to severe acute malnutrition in hospitalized under 5 children and to find out socio-epidemiological characteristics and disease profile in the same group. Methods: This observational study was conducted in a tertiary care teaching hospital on hospitalized children aged 6 months to 5 years. After obtaining informed consent and detail history including epidemiological profile, complete physical examination and anthropometry were recorded. WHO criteria were used for nutritional assessment. Disease profile of the patients was recorded. Results: A total of 230 children were enrolled. Male: Female ratio was 1.64:1; total 153 (66.5%) children were malnourished. The prevalence of MAM and SAM was 28.7% and 20% respectively. Most common diseases were acute gastroenteritis and pneumonia. More than 80% children exhibited anemia. Low birth weight, higher birth order, incomplete immunization, lower socioeconomic status, lower maternal literacy and faulty feeding practices were significantly associated with malnutrition. Conclusions: About 2/3rd admitted children were malnourished and 20% were suffering from SAM. Acute gastroenteritis and pneumonia were most common diseases. There was strong need to educate the family specially mother about nutritional needs of the child. Parents must be counselled about the importance of birth spacing, family planning, immunization and exclusive breastfeeding till 6 months of age.